Relationships between knowledge and attitudes on child abuse and abusive behaviors among parents in Imo State, Nigeria - Nduka, Adolphus Chukwuka (2012)
The purpose of this research was to examine the relationships between parents’ knowledge of child physical abuse, attitudes towards child physical abuse and the abusive behaviors among parents. The study provided research information on the relationships existing between parents’ demographic variables, stress level, cultural values, knowledge of child physical abuse, attitudes towards child physical abuse and the abusive behaviors. A total of 411 respondents were selected through multistage sampling methods to participate in this study. Respondents completed the survey as Dimensions of Disciplinary Inventory (DDI) by Straus and Fauchier (2007) was used to measure parents’ abusive behaviors. Parents’ attitude towards child physical abuse was measured using Parental Attitudes towards Childrearing Questionnaire (PACR) by Goldberg & Easterbrooks' (1988) while parents’ knowledge of child physical abuse was measured using Knowledge of Child Abuse Instrument developed by Garrusi, Safizadeh & Bahramnejad (2007). The results of this study were analyzed using descriptive statistics, Pearson product moment correlations and multiple linear regressions. The findings in this study showed that parental abusive behavior has significant and positive correlations with number of children in the family, cultural values, stress level and parental attitudes towards child physical abuse. The study also found that parental abusive behavior has significant and negative correlations with family income, parents’ years of education and parental knowledge of child physical abuse. Findings of the study further revealed that there is significant and negative correlation between parental attitude towards child physical abuse and knowledge of child physical abuse. Findings from multiple linear regression analysis revealed that 79.5% of parental abusive behaviors were explained by five predictor variables which were parental stress level, parents’years of education, number of children in the family, cultural values, and attitude towards child physical abuse. Based on the Ecological system theory (Bronfenbrener, 1979), the complexities of the psychosocial factors (parenting stress level and cultural values), the demographic variables (number of children in the family, parents’ years of education and family income level), knowledge of physical child abuse and parental attitudes towards child physical abuse within the context of parent-child relationship were more understandable. Future research can expand on other types of child maltreatment such as sexual abuse, emotional/psychological abuse and neglect.